Satellite measurements oversee China’s sulfur dioxide emission reductions from coal-fired power plants - Siwen Wang; Qiang Zhang; Randall V Martin; Sajeev Philip; Fei Liu; Meng Li; Xujia Jiang; Kebin He (Environmental Research Letters, 2015)
To evaluate the real reductions in sulfur dioxide (SO _2 ) emissions from coal-fired power plants in China, Ozone Monitoring Instrument (OMI) remote sensing SO _2 columns were used to inversely model the SO _2 emission burdens surrounding 26 isolated power plants before and after the effective operation of their flue gas desulfurization (FGD) facilities. An improved two-dimensional Gaussian fitting method was developed to estimate SO _2 burdens under complex background conditions, by using the accurate local background columns and the customized fitting domains for each target source. The OMI-derived SO _2 burdens before effective FGD operation were correlated well with the bottom-up emission estimates ( R  = 0.92), showing the reliability of the OMI-derived SO _2 burdens as a linear indicator of the associated source strength. OMI observations indicated that the average lag time period between installation and effective operation of FGD facilities at these 26 power plants was around 2 years, and no FGD facilities have actually operated before the year 2008. The OMI estimated average SO _2 removal equivalence (56.0%) was substantially lower than the official report (74.6%) for these 26 power plants. Therefore, it has been concluded that the real reductions of SO _2 emissions in China associated with the FGD facilities at coal-fired power plants were considerably diminished in the context of the current weak supervision measures.